2017
DOI: 10.1002/jcla.22164
|View full text |Cite
|
Sign up to set email alerts
|

The relation between international normalized ratio and mortality in acute pulmonary embolism: A retrospective study

Abstract: Elevated INR may have prognostic value for 30-day mortality in acute PE patients not on anticoagulation. Combining INR with sPESI score improved the predictive value for all-cause mortality. However, further large-scale studies are needed to confirm it's prognostic role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This finding was further confirmed in retrospective calculation of sPESI, that predicts 30-day mortality of PE patients 1 . Therefore, this study is consistent with previous that confirmed INR as parameter helpful in reclassification of PE patients into more appropriate risk groups 13,18,19 , that should translate into more careful inhospital as well as long-term outpatient care, that might result in an improvement of post-PE patients survival.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding was further confirmed in retrospective calculation of sPESI, that predicts 30-day mortality of PE patients 1 . Therefore, this study is consistent with previous that confirmed INR as parameter helpful in reclassification of PE patients into more appropriate risk groups 13,18,19 , that should translate into more careful inhospital as well as long-term outpatient care, that might result in an improvement of post-PE patients survival.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, not all patients had information about previous anticoagulation, therefore the impact of this treatment on INR value can not be investigated. The increase of INR in our investigated population may be a result of overlaping organ impairment including heart failure, liver dysfunction and secondary to neoplasm abnormalities rather than the effect of anticoagulant treatment 13,14,18,19 . The mechanism of INR increase is not fully understood and in our population the data regarding anticoagulation are lacking, therefore this issue requires further research.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, the association of INR on admission with the 90-day mortality of critically ill patients who underwent endarterectomy during hospitalization has been shown [6], and also that the prothrombin time-albumin ratio (PTAR) predicted 90-day mortality in critically ill patients with liver cirrhosis [7]. Another study reported that prolonged initial prothrombin time or higher INR in the absence of anticoagulant therapy was associated with all-cause mortality in patients with acute coronary syndrome who were undergoing percutaneous coronary intervention [8] and the INR has been shown to be associated with mortality in acute pulmonary embolism [9].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary embolism (PE) is the only preventable cause of death in hospitalized patients with 15% mortality rate, which increases to 25% among hemodynamically instable cases (1)(2)(3). It kills 200 to 300 thousands a year worldwide.…”
Section: Introductionmentioning
confidence: 99%